Propiedad constitucional, a propósito de la fe pública registral - Mejorada Chauca, Martín (Pontificia Universidad Católica del Perú, 2015)
Concerning the constitutional property right, doesour current Constitution only protect the owners ordoes it also protect, for example, the usufructuaries and superficiaries? Is this related to Public Trust In Registration and the protection given to the bonafides third party acquirers?In this article, the renowned author answers these questions, considering the current constitutional economic regime and the changes made in relation to the Constitution of 1979 regarding the property right.

En cuanto al derecho constitucional de propiedad¿la Constitución actual protege sólo a los propietarios o también a, por ejemplo, los usufructuarios y superficiarios? ¿Tiene ello relación con la Fe Pública Registral y la protección a los terceros adquirentes de buena fe?En el presente artículo, el renombrado autor da respuesta a estas preguntas, teniendo en cuenta el régimen económico constitucional y los cambios producidos respecto a la Constitución de 1979 con relación al derecho de propiedad.
Constitutional property, regarding public trust in registration
Keywords: Derecho; https://purl.org/pe-repo/ocde/ford#5.05.01